find their factorisation
Attachments:
![](https://hi-static.z-dn.net/files/d57/28750316f60ad7de4f5bb2795bfc721e.jpg)
Answers
Answered by
3
Here is ur solution
3a2+4ab+b2−2ac−c2
= 4a2+4ab+b2−a2−2ac−c2
= (2a+b)2−(a+c)2= (2a+b+a+c).(2a+b−a−c) [Since A2−B2=(A−B).(A+B)]
= (3a+b+c).(a+b−c)
Mark this as brainliest
3a2+4ab+b2−2ac−c2
= 4a2+4ab+b2−a2−2ac−c2
= (2a+b)2−(a+c)2= (2a+b+a+c).(2a+b−a−c) [Since A2−B2=(A−B).(A+B)]
= (3a+b+c).(a+b−c)
Mark this as brainliest
amish90:
4a2 kaha se aa rha hai
Similar questions